Why travel far to learn? A study of environmental behaviour change experience of residential outdoor environmental education participants - Syed-Abdullah, Sharifah Intan Sharina (Routledge, 2023)
Residential outdoor environmental education (ROEE) is commonly used to educate people about the environment. This research focuses on the participants’ subjective perceptions of the impact of the drag and drop approach used in ROEE courses on changing their environmental behaviour and the extent to which the changes (if any) are sustained. The study adopted a narrative approach and used the transtheoretical model (TTM) as the theoretical framework for the investigation. Eleven former participants of the ROEE courses were interviewed. The interview data were analysed by using the method of individual narrative and thematic analysis. The study found that the ROEE courses did not change the participants’ environmental attitudes and behaviour in a significant way due to three explanations: i) sociocultural differences between locations; ii) unsuitable contents, and iii) discontinued learning experience and intervention. This study provides extensive suggestions of how the practice of ROEE courses can be improved which is based on the participants’ narrative of unsuccessful learning intervention approaches.